Generation of runoff hydrographs for uniform and non-uniform temporal rainfall intensity distribution - Pham, Nguyen Anh (2018)
With the rapid development in urban areas, more and more surface areas that once used to absorb rainfall and impede flow movement through the catchment are replaced by the impervious area. This leads to the need of designing sustainable urban drainage system to drain the excess rainwater and reduce the consequences caused by the surface runoff. In Singapore, the design is based on the Rational Formula. However, the Rational Formula does not represent the whole picture of a rainfall event, so it may be not suitable to be used in the design of drainage system. Other methods have been proposed to develop the runoff hydrograph, and hence the peak flow, to give a more conservative result. This study is sought to generate runoff hydrographs for uniform and non-uniform temporal rainfall intensity distribution. Different rainfall distributions such as Chicago hyetograph, Huff rainfall distribution, Synthetic Block-Design Storm hyetograph, and Yen & Chow hyetograph are used to produce synthetic rainfall profiles. Two methods, Storm Water Management Model (SWMM) by US EPA, and Modified Rational Method (MRM), are employed in the study to generate the hydrographs and predict the peak flows. The results show that SWMM give higher peak flows than MRM and Rational Formula. The time to peak given by SWMM is also faster than MRM. Generally, the peak flows predicted by SWMM are more sensitive to the changes in sub-catchment’s characteristics when the rainfall duration is shorter. However, the generated rainfall hyetographs and runoff hydrographs are based on methods that are only calibrated for use in the US. Hence, the results may not be truly reflect the meteorological patterns in Singapore. Therefore, further studies that use Singapore’s rainfall profile are required to increase the reliability of the results.